Custom Queueing method for enhancing security of a Packet Scheduling Process in Real Time Networks - G.Karuna,; Swaraja K, (International Journal of Psychosocial Rehabilitation, 2020)
The wireless technologies became a part of our day to day life, for sending and sharing data very rapidly so that everyone today uses wireless networks for their business or personal. The traditional wireless communication technology is unable to satisfy real-time transmission requirements in mobile electronic commerce application such as access of books from digital libraries, access of stock exchange information etc. Recent real time wireless networks require high level security to guarantee the information passed through wireless channels. So, designing flexible security mechanisms for real time applications and transmitting packets through wireless networks is highly desirable. The present work introduces a new packet scheduling algorithm to enhance security which mainly aims to dynamically determine security levels of packets based on security requirements of an application and also guaranteeing deadlines for packets. By incorporating Custom Queuing method with this packet scheduling algorithm, the overall performance of real time networks is increased